A study on the effects of herbal acupuncture with Liriopis Tuber extract on airway inflammation in the mouse induced with bronchial asthma - Young-Whan Park; Hee-Soo Park (Korean Pharmacopuncture Institute, 2001)
Objectives: Herbal acupuncture has been administered with Liriopis Tuber extract on the point of BL 13 (Pyesu) to treat bronchial asthma and a certain degree of clinical benefits have been observed but lacking scientific substantiation. Methods: The present report describes on Th1 cytokine (Interleukin-2, Interferon-gamma), Th2 cytokine, (Interleukin-4, Interleukin-5), and IL-12 in bronchoalveolar lavage fluid (ELISA). Five groups were devised to study the effects of herbal acupuncture with Liriopis Tuber extract at BL 13 (Pyesu) for airway inflammation in the mouse model with bronchial asthma. Results shows that herbal acupuncture with Liriopis Tuber extract at BL 13 increased Th1 cytokine (Interleukin-2) in allergic sensitization and allergic challenge, and decreased Th2 cytokine (Interleukin-2, Interleukin-5) in allergic sensitization.